Morphometry of skeletal muscle capillaries: the relationship between capillary ultrastructure and ageing in humans. (16th June 2016) - Bigler, M.; Koutsantonis, D.; Odriozola, A.; Halm, S.; Tschanz, S. A.; Zakrzewicz, A.; Weichert, A.; Baum, O.
Abstract: Aim: To determine whether the ultrastructure of the capillary system in human skeletal muscle changes during advancing senescence, we evaluated the compartmental and subcompartmental organization of capillaries from vastus lateralis muscle (VL) biopsies of 41 non‐diseased persons aged 23–75 years. Methods: From each VL biopsy, 38–40 randomly selected capillaries were assessed by transmission electron microscopy and subsequent morphometry with a newly established tablet‐based image analysis technique. Results: Quantification of the compartmental organization revealed most indicators of the capillary ultrastructure to be only non‐significantly altered ( P  >   0.05) over age. However, the peri‐capillary basement membrane (BM) was thicker in the older participants than in the younger ones ( P  ≤   0.05). Regression analysis revealed a bipartite relationship between the two parameters: a homogenous slight increase in BM thickness up to the age of approximately 50 years was followed by a second phase with more scattered BM thickness values. In 44.5% of the capillary profiles, projections/filopodia of the pericytes (PCs) traversed the BM and invaded endothelial cells (ECs) visible as PC pegs in pale cytoplasm holes (EC sockets). Strikingly, PC pegs were often in proximity to the EC nucleus. In PC profiles, sockets were likewise detected in 14.2% of the capillaries. Within these PC sockets, cellular profiles were frequently seen, which could be assigned to EC filopodia, internal PC curling or PC–PC interactions. Quantification of the occurrence of peg–socket junctions revealed the proportions of empty EC sockets and empty PC sockets to increase ( P  ≤   0.05) during ageing. Conclusion: Our investigation demonstrates advancing senescence to be associated with increase in BM thickness and loss of EC and PC filopodia length in skeletal muscle capillaries.